Husserl on Foundation - Correia, Fabrice (My University, 2004)
In the third of his Logical Investigations, Husserl draws an important distinction between two kinds of parts: the dependent parts like the redness of a visual datum or the squareness of a given picture, and the independent parts like the head of a horse or a brick in a wall. On his view, the distinction is to be understood in terms of a more fundamental notion, the notion of foundation. This paper is an attempt at clarifying that notion. Such attempts have already been undertaken (separately) by Peter Simons and Kit Fine, and the paper also contains elements of comparison of our three sets of views.